Kontribusi Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah di Provinsi Jawa Timur - Hari Setiono (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
Local tax is a compulsory contribution owed by an individual or an entity to finance local government administration and development. Local Levy is one of the Original Revenue as a source of financing the implementation of government and regional development, to improve and state the welfare of the community. The original revenues of the regions are all receipts obtained by the region from sources within its own territory which are levied according to the local regulations in accordance with the prevailing laws and regulations. This research is a quantitative descriptive type that aims to describe the data of research in the form of numbers by way of describing it to know the contribution of local taxes and levies to local revenue originated in PERDA APBD East Java Province from 2013 until 2016. Research is described in the form table to find out how much the percentage of local tax contribution and levy to PAD. The results of the year 2013-2016 average local taxes contribute 83.49% and local levies contribute 0.98%. The highest tax contribution is 2015 of 85.24% and the highest levy contribution is in 2013 at 1.33%